2009
DOI: 10.1152/ajpgi.90464.2008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of CD4+T cell subsets in hepatic ischemia/reperfusion injury

Abstract: Kuboki S, Sakai N, Tschöp J, Edwards MJ, Lentsch AB, Caldwell CC. Distinct contributions of CD4 ϩ T cell subsets in hepatic ischemia/reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 42 publications
6
70
0
1
Order By: Relevance
“…14 Adoptive transfer studies showed that CD73 KO Tregs, which cannot convert adenosine monophosphate to adenosine, are unable to protect WT mice from kidney IRI. 37 47,54 having no effect in other studies, 48,51,52 and protecting from injury in one ischemic stroke study. 46 The reasons for conflicting results between studies in the same organ may be technical differences in the injury models (e.g., severity of injury in control mice) or methods of Treg depletion (e.g., PC61 versus diphtheria toxin-mediated depletion of FoxP3 + Tregs).…”
Section: Role Of Adenosine In Treg-mediated Kidney Protectionmentioning
confidence: 86%
“…14 Adoptive transfer studies showed that CD73 KO Tregs, which cannot convert adenosine monophosphate to adenosine, are unable to protect WT mice from kidney IRI. 37 47,54 having no effect in other studies, 48,51,52 and protecting from injury in one ischemic stroke study. 46 The reasons for conflicting results between studies in the same organ may be technical differences in the injury models (e.g., severity of injury in control mice) or methods of Treg depletion (e.g., PC61 versus diphtheria toxin-mediated depletion of FoxP3 + Tregs).…”
Section: Role Of Adenosine In Treg-mediated Kidney Protectionmentioning
confidence: 86%
“…Using warm and cold hepatic I/R models, studies have shown different roles for liver-resident versus blood-borne DCs, highlighting the importance of the local microenvironment in determining DC function during hepatic IRI [6-8]. Additionally, a previous study determined that CD4+ T cells play an important role in liver IRI [9]. Activated CD4+ T cells exhibit various immune functions with distinctive phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Kupffer cells and hepatocytes also generate ROS, leading to direct damage of endothelial cells and hepatocytes. Due to their important role, ROS levels are tightly regulated through different pathways 33. The major regulators are ROS scavengers that include SOD, catalase, and glutathione peroxidase (GSH-Px).…”
Section: Discussionmentioning
confidence: 99%